Antibacterial Activity and Multi-Targeting Mechanism of Dehydrocorydaline From Corydalis turtschaninovii Bess. Against Listeria monocytogenes - Kim, Gowoon; Xu, Yijuan; Zhang, Jiarong; Sui, Zhongquan; Corke, Harold (Frontiers in Microbiology, 2022)
Listeria monocytogenes is a foodborne pathogen, with relatively low incidence but high case-fatality. Phytochemicals have been recognized as a promising antimicrobial agent as an alternative to synthetic chemicals due to their safety and high efficacy with multi-target sites. This study identified and characterized a novel antibacterial agent, dehydrocorydaline, in Corydalis turschaninovii rhizome using HPLC-LTQ-Orbitrap-HRMS and its antibacterial effect with lowest MIC (1 mg/mL) and MBC (2 mg/mL) values. In addition, in vitro growth kinetic assay, cytoplasmic nucleic acid and protein leakage assay and observation of morphological changes in bacterial cells supported the strong antibacterial activity. In order to investigate potential antibacterial mechanism of action of dehydrocorydaline against L. monocytogenes, label-free quantitative proteomics was used, demonstrating that dehydrocorydaline has multiple targets for combating L. monocytogenes including dysregulation of carbohydrate metabolism, suppression of cell wall synthesis, and inhibition of bacterial motility. Moreover, molecular docking analysis confirmed that dehydrocorydaline acts as the inhibitor of MurG involved in bacterial cell wall synthesis. Overall, this study demonstrated that dehydrocorydaline has potential as a natural and effective antibacterial agent with multi-target sites in pathogenic bacteria, and provides the basis for development of a new class of antibacterial agent.